PEMBANGUNAN INFRASTURKTUR IKN BERWAWASAN EKOLOGI QUR’ANI - Umiari, Fahrurozi; Yuwapini, Hamdan; Kholilullah, Mohammad; Huda, Ade Nailul (State Islamic University of Datokarama Palu, 2024)
The relocation of the country's capital from Jakarta to East Kalimantan as an effort to equalize the economy has reaped pros and cons from various groups. Several experts and LSM assess that the development of the National Capital City (IKN) infrastructure will have a negative impact on local communities and the existing ecosystem. However, in order to ward off these concerns, the government has formulated Law Number 3 of 2022 concerning the National Capital which explains that the IKN construction principle is 100% environmentally friendly construction for all its buildings, both residential and commercial buildings, and there will also be the application of appropriate resource practices. efficient and low carbon. The Al-Qur'an, which contains a set of values and guidelines for pursuing the path of improvement (QS. Al-Baqarah [2]: 185), also does not forget to explain ecological principles -albeit cursorily-, as basically the expanse of the earth and everything created in it by Allah swt. use it to gain benefits from it and fulfill human needs (QS. Al-Hijr [15]: 19-20). This research tries to explain the ecological values and principles contained in the Al-Qur'an, so it is hoped that this research can also provide input in the context of developing IKN infrastructure, so that in the development process it does not violate the values and guidelines of ecological signs contained therein. This research uses the maudhu'i (thematic) interpretation method. The research results show that development can be said to be in harmony with the spirit of the Koran when in the process and even after construction it does not threaten the survival of animals, also protects the preservation of plants, maintains cleanliness and does not cause environmental pollution.